PENERAPAN MODEL TALKING STICK PADA MATERI JENIS–JENIS PEKERJAAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MIN 7 PIDIE - Gusti Handayani (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This study aims to determine the application of the Talking Stick model and to determine the improvement of fourth grade student learning outcomes on the types of work in grade IV MIN 7 Pidie. This type of research is Classroom Action Research (CAR) with the research subjects being class IV students of MIN 7 Pidie in the 2019/2020 academic year, totaling 24 students. The data collection techniques used are observation, interviews, documentation and tests. From the results of the study, it was found that in the first cycle the average value obtained by students was 59.37 and classical completeness obtained by students was 33.33%. In the second cycle the average value obtained by students is 88.08 and the classical completeness obtained by students is 100%.